Relationship between the MELD score with severity erectile dysfunction in cirrhotic patients - Doddy Afprianto; Siti Nurdjanah; Muhammad Robikhul Ikhsan (Faculty of Medicine Universitas Gadjah Mada, 2017)
Background. Liver cirrhosis is a pathological condition that describes the end stage of hepatic fibrotic which progressively ongoing that signed by distortion from hepar architecture and the formation of the regenerative modulus. Liver cirrhosis causes impairment in most of the liver function including the hormonal balance and metabolism of steroids. In the male patients, liver cirrhosis causes hypogonadism and feminization. Sexual dysfunction in cirrhotic patients is still underestimated and underdiagnosed. The most common sexual dysfunction in male cirrhotic patients is impotence or erectile dysfunction. Erectile dysfunction (ED) is define as a persistence inability to reach and/ or maintain enough erection to satisfy the sexual activity. International Index of Erectile Function 5/IIEF-5 could mark erectile dysfunction. Despite the prevalence of erectile dysfunction is high in patients with liver cirrhosis, only a few studies revealing the relationship between severity of liver cirrhosis and severity of erectile dysfunction.Objective. The purpose of this study is to determine the correlation between MELD score and severity of erectile dysfunction (IIEF-5 score) in cirrhosis patients.Methods. This study is observational with a cross-sectional method. Subjects were patients with liver cirrhosis, male, age 18 to 65 years old, married, have a partner, and agreed participated to this study. We used Pearson the correlation to assess correlation between severity of liver cirrhosis (Child Pugh score) and severity of erectile dysfunction (IIEF-5 score) if the data were distributed normally and Spearman correlation if the distribution is abnormal.Conclusion. There is negative correlation with the moderate strength degree between MELD score (the degreee of severity in liver cirrhosis) with the IIEF-5 score (the degree of erectile dysfunction). Keywords: liver cirrhosis, MELD score, erectile dysfunction, IIEF-5, correlation.